The Relationship between Spiritual Health and Loneliness among the Elderly in Karaj- 2016 - Nahid Kavoosian; Kazem Hosseinzadeh; Hadigheh Kazemi Jaliseh; Asghar Karboro (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective: Loneliness, which is a common problem among the elderly, severely affects their health. Spiritual health plays an important role in the degree and quality of loneliness among the seniors. This study was conducted to explore the relationship between spiritual health and loneliness among the elderly people in Karaj in 2016. Method: This cross-sectional study adopted a descriptive-analytical design. Through simple sampling method, 275 people who attended seniors' care center in Karaj took part in the study. Standard questionnaires were used to assess the participants' spiritual health and loneliness. All the collected data were codified. Measures of central tendency and dispersion and Pearson correlation were used for data analysis. All ethical issues were observed and the researchers declared no conflict of interests. Results: In total, 71% (n=196) of respondents were male, most of them (93%=256 participants) were married, 56% (n=154) were retired and 82% (226 respondents) had educational levels lower than Diploma. The mean and standard deviation of the participants' spiritual health and loneliness respectively were 99.39±9.56 and 3.47±11.29. Furthermore, a significant, reverse relationship was detected between spiritual health and loneliness. That is, the elderly who enjoyed higher levels of spiritual health experienced lower degrees of loneliness (r=0.33, R2=10.89, p=0.001). Conclusion: The obtained results indicate that designing plans to promote spiritual health among the elderly can play a crucial role in reducing their loneliness. It is recommended that researchers conduct further studies on the elderly's spiritual health. For downloading the full-text of this article please click here.